Respuesta :

Step-by-step explanation:

(7/9a+9/7b)^2 -ab

simplifying (7/9a+9/7b)^2

expanding the bracket

[tex] = ( \frac{7}{9a} + \frac{7}{7b} ) \: ( \frac{7}{9a} + \frac{7}{7b} ) - ab[/tex]

[tex] = \frac{49}{81 {a}^{2} } + \frac{49}{63ab} + \frac{49}{63ab} + \frac{49}{49 {b}^{2} } - ab[/tex]

[tex] = \frac{49}{81 {a}^{2} } + \frac{98}{63ab} + {b}^{2} - ab[/tex]

factorizing b out

49/81a^2 +98/63ab +b(b-a)

the l.c.m= (81a^2) (63ab)

multiplying through by the L.C.M

63ab×49 +98×81a^2 +b(b-a) ×81a^2 ×63ab

... the app is not working anymore

=